Strengthening Tourism Village Governance through Community Participation for Sustainable Development - Yohanes Martono Widagdo; Markus Utomo Sukendar; Sopingi Sopingi (GUYUB: Journal of Community Engagement, 2025)
Sustainable tourism development requires community-based management of tourism villages that is grounded in local potential. Sewu Kembang Tourism Village faces challenges related to weak institutional capacity, limited human resources, and suboptimal utilisation of tourism assets. This community service programme aims to strengthen tourism village governance through a Participatory Action Research (PAR) approach, which positions the community as the main actor throughout the intervention process. The PAR method was implemented through four iterative stages: participatory problem identification and potential mapping, collaborative action planning, action implementation through training and technical assistance, and participatory reflection and evaluation. The programme involved local communities, Pokdarwis, village government, and universities as collaborative partners. The findings indicate significant improvements in human resource capacity, institutional strengthening of Pokdarwis, and increased community participation in tourism management. These improvements were measured through pre- and post-tests, performance observations, and the application of newly acquired skills in destination management practices. The results demonstrate that PAR is an effective approach for fostering community empowerment and supporting the sustainability of tourism village development.